Lactoferrin for COVID-19 prevention, treatment, and recovery - Bolat, Ecem; Eker, Furkan; Kaplan, Merve; Duman, Hatice; Arslan, Ayşenur; Saritaş, Sümeyye; Şahutoğlu, Arif Sercan; Karav, Sercan (Frontiers in Nutrition, 2022)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2), a unique beta-coronavirus, has caused the most serious outbreak of the last century at the global level. SARS-CoV-2 infections were firstly reported in the city of Wuhan in China in 2019 and this new disease was named COVID-19 by World Health Organization (WHO). As this novel disease can easily be transmitted from one individual to another via respiratory droplets, many nations around the world have taken several precautions regarding the reduction in social activities and quarantine for the limitation of the COVID-19 transmission. SARS-CoV-2 is known to cause complications that may include pneumonia, acute respiratory distress syndrome (ARDS), multi-organ failure, septic shock, and death. To prevent and treat COVID-19, some significant studies have been conducted since the outbreak. One of the most noticeable therapeutic approaches is related to a multifunctional protein, lactoferrin. Lactoferrin (Lf) is an 80 kDa cationic glycoprotein that has a great range of benefits from improving the immunity to antiviral effects due to its unique characteristics such as the iron-binding ability. This review summarizes the characteristics of SARS-CoV-2 and the potential applications of Lf for the prevention, treatment, and recovery of COVID-19.